Higgs phenomenon for higher spin fields on AdS3 - Creutzig, Thomas; Hikida, Yasuaki (Journal of High Energy Physics, 2015)
Abstract: In a previous work, a marginal deformation of 2d coset type model with N=3 N=3 superconformal symmetry was studied, and it was interpreted as a change of boundary conditions for bulk fields in the dual higher spin theory. The deformation breaks generic higher spin gauge symmetry, and the generated mass of a spin 2 field was computed. The deformation might be related to the introduction of finite string tension in a superstring theory. In this paper, we extend the analysis and compute the masses of generic higher spin fields at the leading order of 1/c (c is the CFT central charge) but at the full order of the deformation parameter. We find that the masses are not generated for so(3)R singlet higher spin fields at this order and the spectrum is the Regge-like one for so(3)R triplet higher spin-charged fields.
CRIS-Team Scopus Importer:2024-06-24
Keywords: AdS-CFT Correspondence; Conformal and W Symmetry; Higher Spin Gravity; Higher Spin Symmetry